The effect of supplementation of Jackfruit leaves (Artocarpus heterophyllus) and Mashkalai (Vigna mungo) bran to common grass on the performance of goats - Islam, M.; Chowdhury, S.A.; Alam, M.R.; Silong, S. (Asian-Australasian Association of Animal Production Societies, 1997)
The effect of supplementation of Jackfruit (Artocarpus heterophyllus) tree leaves and mashkalai (Vigna mungo) barn on the intake and digestibility of freshly cut common grass by Black Bengal goats was evaluated. Twelve castrated goats of approximately 5-6 months age were randomly allocated to three dietary treatments: freshly cut common grass ad libitum, common grass+100g Jackfruit tree leaves and common grass+100g mashkalai bran. Although digestibilities of dry matter, organic matter, nitrogen and neutral detergent fibre were very similar in the grass alone and mashkalai bran supplemented goats but the values were significantly (p < 0.01) higher than those observed in the Jackfruit leaves supplemented goats. Supplementation of mashkalai bran promoted higher (p < 0.05) digestible nutrients intake with the consequent higher daily live weight gain (75 g) than those fed grass alone (31 g) or supplemented with Jackfruit tree leaves (30 g). It could be concluded that mashkalai bran could be a suitable supplement for goats consuming common grass in the tropics and subtropics.